An Aggregate Cluster‐Dispersed Electrolyte Guides the Uniform Nucleation and Growth of Lithium at Lithium Metal Anodes. Issue 41 (2nd November 2018) - Lee, Min‐Suk; Roev, Victor; Jung, Changhoon; Kim, Ji‐Rae; Han, Sangil; Kang, Hyo‐Rang; Im, Dongmin; Kim, Il‐Seok
Abstract: Rechargeable lithium metal battery technology is widely recognized as being a suitable candidate for replacing lithium ion batteries. A critical barrier preventing its application to electrical storage systems is that lithium grows irregularly, which is the fundamental cause of poor characteristics during a battery's lifetime, and also causes safety concerns. There are two reasons for the irregular growth of lithium: lithium prefers to nucleate on specific surfaces; subsequently, the lithium atoms grow rapidly from any protrusions. To suppress such irregularities in electroplating, we combined two approaches; applying a coating of lithiophilic metal to a substrate that would otherwise attract the nucleation of lithium, and using an electrolyte in which aggregate clusters are dispersed, with strongly solvated ionic liquids enclosed by another solvent such as a hydrofluoroether. Together, these are intended to guide the uniform nucleation and growth of lithium. By tuning the combination of the two approaches, it was concept proven that lithium would nucleate and grow more uniformly than on a pristine Cu or Ni substrate. Abstract : The effect of hydrofluoroether (HFE) to the electrolyte system based on 1, 2‐dimethoxyethane (DME) and lithium bis(fluorosulfonyl)imide (LiFSI) was studied. HFE is not able to dissolve the salt, but is mixed with DME. As the proportion of HFE has been increased, the Raman shift is moving toward LiFSI, indicating that free bis(fluorosulfonyl)imide (FSI) anions can be converted to aggregate forms insoluble in electrolyte. With such a replacement, uniform electrodeposition of Li can be achieved, even if the concentration of its salt is 1 mol L ‐1 .